Why Has the Ability to Regenerate Following CNS Injury Been Repeatedly Lost Over the Course of Evolution? - Blackshaw, Seth (Frontiers in Neuroscience, 2022)
While many vertebrates can regenerate both damaged neurons and severed axons in the central nervous system (CNS) following injury, others, including all birds and mammals, have lost this ability for reasons that are still unclear. The repeated evolutionary loss of regenerative competence seems counterintuitive, and any explanation must account for the fact that regenerative competence is lost in both cold-blooded and all warm-blooded clades, that both injury-induced neurogenesis and axonal regeneration tend to be lost in tandem, and that mammals have evolved dedicated gene regulatory networks to inhibit injury-induced glia-to-neuron reprogramming. Here, different hypotheses that have been proposed to account for evolutionary loss of regenerative competence are discussed in the light of new insights obtained into molecular mechanisms that control regeneration in the central nervous system. These include pleiotropic effects of continuous growth, enhanced thyroid hormone signaling, prevention of neoplasia, and improved memory consolidation. Recent evidence suggests that the most compelling hypothesis, however, may be selection for greater resistance to the spread of intra-CNS infections, which has led to both enhanced reactive gliosis and a loss of injury-induced neurogenesis and axonal regeneration. Means of testing these hypotheses, and additional data that are urgently needed to better understand the evolutionary pressures and mechanisms driving loss of regenerative competence, are also discussed.